Extracting contact recombination from FFT-filtered photoluminescence imaging of half-metallised silicon solar cells - Shi, Y; Payne, DNR; Fell, A; Leon, C; Niewelt, T; Khorani, E; Wilshaw, PR; Murphy, JD; Okamoto, K; Bonilla, RS (Royal Society of Chemistry, 2025)
In high-performance Si solar cells, recombination at the metal-silicon interface has become the major remaining barrier to reaching the theoretical power conversion efficiency limit. Efficient and practical assessment of metal-associated recombination is crucial for understanding and mitigating these losses. This study presents a photoluminescence imaging-based method for evaluating the metal contact recombination current (J0,c) of rear TOPCon metallisation. The proposed method is based on the Fourier analysis of the periodic pattern corresponding to the metal fingers on samples. This requires no specially designed metallisation geometries. Noise normalisation and bandpass filtering in k-space are used to suppress noise and preserve the metal contrast signal. Numerical device simulations are used to establish the relation between contact recombination levels and the resulting metal contrasts in photoluminescence images. Testing this technique using data from samples made with two different metallisation pastes demonstrates the differences in contact recombination J0,c values, showing the practical application of the technique. Experimental conditions, including PL illumination and camera resolution, are discussed to determine their influence on the efficacy of the proposed method. This Fourier analysis-based J0,c determination method is well-suited for industrial finger grid metallisation and has the potential to enable seamless contact characterisation for PV manufacturing.